Sensitivity of Junction Width to Tidal Nonlinearity on Small and Shallow Tidal Junction - Faruq Khadami; Kiyosi Kawanisi; Mohamad Basel Al Sawaf; Gillang Noor Nugrahaning Gusti (Universitas Pendidikan Indonesia, 2022)
Observations of water elevation in the short and small tidal junctions of the Ota River, Japan, showed an increase in tidal nonlinearity at the apex of the junction. To quantitatively estimate the increase in nonlinearity, the barotropic hydrodynamic model was applied in an idealized junction domain, inspired by the Ota River Estuary junction. Even though the model was simplified, it successfully reproduced the increase in nonlinearity at the junction apex. A sensitivity analysis of tidal nonlinearity to the width of the upstream channel at the junction was performed by varying the upstream channel width from the same width as the branch channel width to three times the branch channel width. The relationship between the upstream channel width at the apex and tidal nonlinearity was not linear. Tidal nonlinearity was maximized when the apex width was twice the branch channel width. The convergence of the tides in the small width junction induced an increase of some positions of quarter-diurnal tidal constituent that raised the tidal nonlinearity. In the case of a wider channel, the flushing from river runoff dampen the tidal constituents, making it decrease tidal nonlinearity